2017
DOI: 10.1128/mbio.00540-17
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin Combinations Combat Escherichia coli Harboring mcr-1 and bla NDM-5 : Preparation for a Postantibiotic Era

Abstract: The rapid increase of carbapenem resistance in Gram-negative bacteria has resurrected the importance of the polymyxin antibiotics. The recent discovery of plasmid-mediated polymyxin resistance (mcr-1) in carbapenem-resistant Enterobacteriaceae serves as an important indicator that the golden era of antibiotics is under serious threat. We assessed the bacterial killing of 15 different FDA-approved antibiotics alone and in combination with polymyxin B in time-killing experiments against Escherichia coli MCR1_NJ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 37 publications
2
38
0
1
Order By: Relevance
“…[106][107][108][109] With the recent report of mobile colistin resistance genes, 16-18, 110, 111 the presence of heteroresistance, 19 and the association between colistin resistance and increased risk of in-hospital mortality, 106 there is mounting support for strategies to optimize polymyxins therapeutically including combination therapy. 41,[111][112][113] There is a mechanism-based rationale for using polymyxins in combination with other antimicrobials that display synergy with a membrane permeabilizer (such as the polymyxins) allowing for increased concentrations of companion antibacterial agents that have intracellular targets. 109,[114][115][116] Unfortunately, the clinical literature on combination therapy versus monotherapy is difficult to interpret due to limitations in many studies.…”
Section: Polymyxin Combinationsmentioning
confidence: 99%
“…[106][107][108][109] With the recent report of mobile colistin resistance genes, 16-18, 110, 111 the presence of heteroresistance, 19 and the association between colistin resistance and increased risk of in-hospital mortality, 106 there is mounting support for strategies to optimize polymyxins therapeutically including combination therapy. 41,[111][112][113] There is a mechanism-based rationale for using polymyxins in combination with other antimicrobials that display synergy with a membrane permeabilizer (such as the polymyxins) allowing for increased concentrations of companion antibacterial agents that have intracellular targets. 109,[114][115][116] Unfortunately, the clinical literature on combination therapy versus monotherapy is difficult to interpret due to limitations in many studies.…”
Section: Polymyxin Combinationsmentioning
confidence: 99%
“…A time-kill assay revealed that the addition of amikacin is able to restore the susceptibility of four NDM-positive and mcr-positive E. coli strains to colistin (258). However, another time-kill assay demonstrated that the combination of amikacin and polymyxin B failed to eradicate NDM-positive and mcr-positive E. coli strains but that the addition of aztreonam with amikacin and polymyxin achieved eradication (274).…”
Section: Polymyxins (Colistin and Polymyxin B) Alone And In Combinationmentioning
confidence: 99%
“…Another method appears to be the mainstream approach involving the effective administration of colistin as well as the potential use of combination therapies with additional agents to generate synergistic associations. These agents can include antibiotics that are typically restricted for use against gram-positive bacteria, such as amikacin (Bulman et al 2017;Zhou et al 2017 (Hu et al 2019), and derivatives of tryptamine (Barker et al 2019). Alternatively, natural products acting as adjuvants can be used, some of which can interact with lipopolysaccharides to perturb the outer bacterial membrane, such as pentamidine (Stokes et al 2017) and meridianin D analogs (Huggins et al 2018).…”
Section: Implications For Drug Designmentioning
confidence: 99%